A STUDY OF STUDENTS’ ATTITUDES TOWARDS ENGLISH LECTURERS’ CODE SWITCHING IN THE CLASSROOM - Montalia, Vinny Elisia; Purwanti, Indah Tri; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aimed to analyse English department students' attitudes towards their lecturers' code-switching at Universitas Riau and its perceived impact on learning motivation and English development. Employing a quantitative survey design, data were collected from 73 third-year students using a 30-item questionnaire adapted from AlQaysi (2019), which utilized a 5-point Likert scale. The questionnaire assessed three aspects of attitude: affective, behavioural, and cognitive. Data were analysed using SPSS 25 with descriptive analysis methods. Findings revealed that students generally held positive attitudes towards code-switching, particularly in the affective aspect (mean score 3.768), while exhibiting neutral attitudes in behavioural (mean score 3.341) and cognitive (mean score 3.456) aspects. The overall mean score of 3.521 indicated a positive attitude towards code-switching. This positive perspective, despite neutral scores in behavioural and cognitive areas, highlights the significant influence of students' favourable emotional responses. The study concludes that while code-switching may not directly shape students' learning behaviours or cognitive comprehension, its acceptance and emotional appeal are significant enough to foster an overall positive attitude, emphasizing the importance of emotional connection in English learning settings. Keywords: Student attitude, English lecturers, code switching.